Phaegopterina (Erebidae, Arctiinae, Arctiini) em áreas de Cerrado e Amazônia do Estado do Maranhão - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The Arctiini tribe comprises a diverse taxonomic group, relatively well represented in Brazil. In addition, they are among the main Lepidoptera used as bioindicators in monitoring natural ecosystems. Currently, Arctiini encompasses the current subtribes: Arctiina, Ctenuchina, Euchromiina, Callimorphina, Phaegopterina, Pericopina and Spilosomina. The Phaegopterina subtribe includes about 151 genera distributed in 1,720 species for the Neotropical region. The Phaegopterina moths includes approximately 750 species registered in Brazil, for the Cerrado 254 species are registered and for the Amazon 469. In the present study I present an inventory with an annotated list of Phaegopterina species and distribution recorded for Maranhão. The material examined comes from two biological collections: the Maranhão Zoological Collection (CZMA), and the Victor O. Becker Collection (VOB), from collections in 10 municipalities in Maranhão. After analyzing the material in this study, I have a list of 116 species of Phaegopterina, distributed in 57 genera for Maranhão, with 25 species being new records. Updating the number of Phaegopterina records for Maranhão, after this study, I totaled 116 Phaegopterina species recorded for the state. Ongoing inventory efforts for Arctinae in Maranhão will contribute to an increase and understanding of the diversity of Lepidoptera in the Cerrado and Amazon facilitating future work on spatial ecology and species identification, which can help in the conservation of Phaegopterina.
Keywords: Biodiversidade de lepidópteros; Inventário; Mariposas; Registros de espécies; CNPQ::CIÊNCIAS BIOLÓGICAS